Variation of false twist on spinning process stability and resultant yarn properties in a modified ring spinning frame. Issue 16 (August 2018) - Yin, R; Tao, XM; XU, BG
Twisting is an important process to form a continuous yarn from short fibers and to determine the structure and properties of the resultant yarn. This article reports on the effect of variation of false twist on process stability and resultant yarn quality in a modified ring spinning frame. Based on twist kinematics, three practical cases that cause twist variations in the spinning process are investigated, namely step function, rectangular function and periodic function changes in false twist. The simulation results are validated by experiments and a good agreement has been demonstrated. The resultant properties of yarn within 30% periodic change in false twist demonstrated insignificance compared with yarn without variation. With the developed model, essential system parameters are numerically examined and their quantitative relationships are studied. The practical implications are discussed.